Ecological classification and mapping for landscape management and science: Foundations for the description of patterns and processes. (February 2016) - Cullum, Carola; Rogers, Kevin H.; Brierley, Gary; Witkowski, Ed T.F.
There is growing demand for biogeographical landscape classifications and ecological maps that describe patterns of spatially co-varying biotic and abiotic ecosystem components. This demand is fuelled by increasing data availability and processing capacity, by institutional practices of land and water resource management and planning and by the growth of transdisciplinary science that requires the development of a shared conceptual framework through which to view landscape character and behaviour. Despite the widespread use of ecological maps, and the extent to which they have become embedded in institutional practice, policy and law, no standard approach to ecosystem mapping has emerged, such that there are many valid ways of mapping the same landscape. Consensus is possible only when there is agreement on the spatial entities to be mapped. We propose a way of defining such entities and identifying them in any given landscape. Landscapes are conceived in terms of a conceptual biophysical template that constrains a wide range of ecological processes at various hierarchical levels. The template is conceived as comprising co-evolved associations of soils, vegetation, topography and hydrology that form a dynamic mosaic characteristic of a particular topographic, climatic and geological context that is continually being shaped by many perturbations. We synthesise themes from vegetation, soil and river sciences, using hierarchy theory to frame a perspective that facilitates the definition of mappable landscape entities at three hierarchical levels of organisation. These entities are conceived as archetypal structural-functional units, with form and process linked in conceptual models that underpin each archetype. We describe how our approach has been used to map ecological entities in Kruger National Park, South Africa, showing how the proposed framework integrates key system components, providing transparent foundations for transdisciplinary approaches to landscape management and science.